The value of intestinal fatty acid binding protein as a biomarker for the diagnosis of necrotizing enterocolitis in preterm infants: a meta-analysis - Li Ren; Mingyan Hei; Hailan Wu; Dan Guo; Shiqi Liu; Qiaoru Zhang; Min Jiang (BMC Pediatrics)
Abstract Background Necrotizing enterocolitis (NEC) is a serious condition mainly affecting newborns, especially preterm or low birth weight ones, with a poor prognosis. The present study aimed to comprehensively evaluate the diagnostic value of intestinal-type fatty acid-binding protein (I-FABP) in NEC through meta-analysis. Methods Relevant documents on the diagnosis of I-FABP in neonatal NEC were retrieved from PubMed, ScienceDirect, Embase, Cochrane, Wanfang, and CNKI databases. Summary receiver operating characteristic curve (SROC), sensitivity, specificity, and likelihood ratio (LR) were constructed to evaluate the pooled diagnostic value. Meta-regression analysis was conducted to explore the sources of heterogeneity. Sensitivity analysis was performed to detect the robustness of current results. Results The present study encompassed 15 studies. I-FABP had a high diagnostic value for NEC, with a sensitivity at 0.78 (0.70–0.85), a specificity of 0.85 (0.78–0.90), and the area under the curve (AUC) value was 0.89 (0.86–0.91). The combined diagnostic odds ratio (DOR) was 20.33 (10.90–37.90) indicating a high diagnostic potential with strong discriminatory power. Sample source, detection method, and critical value might be the source of heterogeneity. There was no significant publication bias. Conclusion I-FABP played a crucial role in diagnosing NEC in premature infants.